2015
DOI: 10.1038/jhh.2015.88
|View full text |Cite
|
Sign up to set email alerts
|

Plasma renin and cardiovascular responses to the cold pressor test differ in black and white populations: The SABPA study

Abstract: Low plasma renin levels and augmented cardiovascular reactivity to stress are common in blacks and have been linked to the development of hypertension in this population. We (i) compared cardiovascular and plasma renin reactivity to a cold pressor test between a black and white population; and (ii) investigated the associations between cardiovascular and plasma renin reactivity within the black and white populations. Our population consisted of 153 black and 188 white men and women (age range, 20-65 years). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We have recently published a detailed review on the advances in understanding the distinct physiological, lifestyle and demographic differences between black and white populations, including dietary, cultural and physiological differences [21] (e.g., suppressed renin [22], increased arterial stiffness [2325], sympathetic nerve activity [26, 27] and an increased inflammatory profile [28, 29] in black populations). Thus, the results from the present study reflect one aspect of an entire array of factors collectively contributing to an adverse cardiovascular pro-file, specifically observed in the black women of this study, and should therefore be interpreted accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently published a detailed review on the advances in understanding the distinct physiological, lifestyle and demographic differences between black and white populations, including dietary, cultural and physiological differences [21] (e.g., suppressed renin [22], increased arterial stiffness [2325], sympathetic nerve activity [26, 27] and an increased inflammatory profile [28, 29] in black populations). Thus, the results from the present study reflect one aspect of an entire array of factors collectively contributing to an adverse cardiovascular pro-file, specifically observed in the black women of this study, and should therefore be interpreted accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated lower levels of plasma renin activity and aldosterone in normotensive African Americans across all ages, with BP positively correlating with plasma aldosterone, an effect that increased as plasma renin activity decreased [48]. Thus, a typical biochemical profile in an African American person with hypertension is a low or high plasma aldosterone concentration, a low or suppressed plasma renin activity or direct renin concentration, and suppressed angiotensin I and II [36,50,54,55]. This results in a normal or elevated aldosterone-to-renin ratio, which can be categorized into two broad hypertension phenotypes: low or suppressed renin and elevated aldosterone (primary aldosteronism type, or hyporeninemic hyperaldosteronism) and low renin and low aldosterone (Liddle syndrome type, or hyporeninemic hypoaldosteronism) [56].…”
Section: Hypertension In African Americans: Clinical Differences Amentioning
confidence: 99%
“…18,19 Many mechanisms have been proposed to explain this, such as a suppressed renin-angiotensin-aldosterone-system and salt sensitivity in black populations. [20][21][22] Based on our previous work in South Africa, 23,24 another possible mechanism could be related to inflammation. Differences in pro-and anti-inflammatory mediator concentrations between ethnic groups have indeed been reported, e.g.…”
Section: Introductionmentioning
confidence: 99%